Associações de cultivares de coentro, cenoura e rúcula sob policultivos em faixas adubados com flor-de-seda - Linhares, Paulo Cássio Alves (2016)
The objective of this research was to evaluate combinations of coriander cultivars, carrot and arugula under polycultures in fertilized strips with roostertree in the conditions of Mossoró-RN. The experiment was carried out from November 2014 to March 2015. The experimental design was a randomized complete block in a factorial 2 x 2 x 2, with four replications. The treatments consisted of the combination of two coriander cultivars ('Verdão' and 'Portuguese') with two carrot cultivars ('Brasilia' and 'Esplanada') and two arugula cultivars ('Cultivada' and 'Folha Larga') in strip-intercropping. The characteristics evaluated in coriander and arugula were: plant height, number of stems or leaves per plant, yield of green mass and dry mass of shoots. In the carrot were analyzed: plant height, number of stems per plant, fresh and dry mass of shoot, dry mass of roots, total production of roots, commercial production of roots and productivity of classified roots (long, medium, short and scrap). In the intercropping system was determined the agronomic efficiency indices and economic indicators: land equivalent ratio, productive efficiency index, score of the canonical variable, gross income, net income, rate of return, profit margin, monetary advantage and modified advantage monetary. A univariate analysis of variance was performed to evaluate the characteristics analyzed. A multivariate analysis of variance was performed on the productivity of vegetables crops to obtain the score of the canonical variable Z. The Tukey test was used to compare the average of the factors treatments. There was no significant interaction between cultivars of coriander, carrot and arugula in any of the characteristics evaluated in the carrot. The best associations were those that involved coriander cultivar 'Portuguese', carrot cultivar 'Esplanada' and arugula cultivar 'Cultivada'. The sole crop system was more productive than the intercropping